FATTY ACID COMPOSITION OF THREE SPECIES OF FRESH WATER FISHES. - GOPAKUMAR, K (Fishery Technology, 2017)
Fatty acid composition of freshwater fish tilapia, (Tilapia mosamhica), barbus (Barbus carnaticus) and Varal (Ophicephalus) is determi:1ed by gas-liquid chromatography. Var:ll contained the highest amount of c20:5 acid compared to other two species. Of the odd-numbered fatty acids c17 was the predominant fatty acid present. Palmitic acid was found to be in a lower level in these fish species compared to marine fish. Barb us recorded unusually high percentage of 23.3% of c18 :2 Acid.